t-(6-4t)=2t+9

Simple and best practice solution for t-(6-4t)=2t+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for t-(6-4t)=2t+9 equation:


Simplifying
t + -1(6 + -4t) = 2t + 9
t + (6 * -1 + -4t * -1) = 2t + 9
t + (-6 + 4t) = 2t + 9

Reorder the terms:
-6 + t + 4t = 2t + 9

Combine like terms: t + 4t = 5t
-6 + 5t = 2t + 9

Reorder the terms:
-6 + 5t = 9 + 2t

Solving
-6 + 5t = 9 + 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.
-6 + 5t + -2t = 9 + 2t + -2t

Combine like terms: 5t + -2t = 3t
-6 + 3t = 9 + 2t + -2t

Combine like terms: 2t + -2t = 0
-6 + 3t = 9 + 0
-6 + 3t = 9

Add '6' to each side of the equation.
-6 + 6 + 3t = 9 + 6

Combine like terms: -6 + 6 = 0
0 + 3t = 9 + 6
3t = 9 + 6

Combine like terms: 9 + 6 = 15
3t = 15

Divide each side by '3'.
t = 5

Simplifying
t = 5

See similar equations:

| 2(7dx+y)=13dx-4y | | -3(x+4)=5x+7-8x+5 | | 3+4=9 | | -47+8x-3x=53 | | 6x+9x-15=180 | | 6x-22=8 | | 13t+t^2+30= | | -9x=-2 | | x^2+16=96 | | 125=5(3x-3) | | -16+24p+7=2p-5 | | 4(1-6m)=148 | | c=hx | | 15=3.00x+.50y | | 1.4x-5.5=1.7-2.2x | | B^2+3=b | | -2(7x+3)=134 | | 4x+3=-2x-9 | | (64k^2)-16k+1=-27 | | 2r-5=2+4r | | -x^2+11x=28 | | -9(x-1)=-3 | | -8(3y+7)=40 | | v^3-3v^2-18v= | | y=-x^2-4x | | x=.36+2.52+.08 | | -180=3x+3(3x-16) | | 22+12-12/3= | | -(8y+4)-(-77-7)=0 | | a/5=-16 | | 4x-4=72 | | 3a+1=-36(a-1) |

Equations solver categories